The Authority of Custom and Habit in Shari'ah Rules in Light of the Jurisprudential Schools - Dr Muhammad Arif Raza; Dr Muhammad Muzammil Imran; Kulsoom Khaleeq Ansari (Journal of Religion and Society, 2025)
The foundation of Islamic law is the divine revelation, which is preserved in the form of the Quran and the Sunnah of the Prophet (peace be upon him). Alongside these primary sources, Islamic jurisprudence has also established principles and regulations to address new issues that arise in different temporal and spatial contexts. Among these principles, "custom and habit" hold a significant and influential status, which scholars have utilized in the extraction and application of Shari'ah rulings.The word (custom) in its linguistic sense refers to something being prominent or well-known, while in its technical sense, it refers to practices or behaviors that are widely accepted and acknowledged in a society, and which are considered appropriate and fitting by those possessing sound intellect and judgment. Similarly (habit) refers to a pattern of behavior that arises from the continuous repetition of a particular individual, group, or society.The role of and has always been a subject of discussion in Islamic jurisprudence, particularly when the question arises whether customs and habits can influence the definitive rulings of Shari'ah. The answer to this question varies among the different jurisprudential schools, which have provided their responses in light of their methodological approaches and principles of ijtihad.It is evident that the primary objective of Shari'ah is the protection of human welfare, taking into account their circumstances and needs. Custom and habit serve as a crucial means in this regard, reflecting the practical life of a particular community or society. For this reason, Islamic jurists have not only considered and in the process of deriving rulings but have also at times used them as a criterion in understanding and applying textual sources.In this article, we will provide a detailed examination of the Shari'ah authority of "custom and habit" in light of the four major Sunni schools of thought: Hanafi, Maliki, Shafi'i, and Hanbali. We will clarify under which conditions custom and habit can be regarded as a valid source of law, and explore the nature and scope of their applicability. Keywords: Habit in Shari'ah, Jurisprudential Schools, Established, Regulations, Methodological, Ijtihad, Islamic Jurists